Echoes among the stones - Wright, Jaime Jo (Bethany House, a division of Baker Publishing Group, 2019)
"After Aggie Dunkirk's career is unceremoniously ended by her own mistakes, she finds herself traveling to Wisconsin, where her grandmother, Mumsie, lives alone in her rambling old home. She didn't plan for how eccentric Mumsie has become, obsessing over an old, unsolved crime scene--even going so far as to re-create it in the attic. Mystery seems to follow her when she finds work as a secretary helping to restore the flooded historical part of the cemetery. Forced to work with the puzzling, yet attractive museum curator to contact living family members of those in the disturbed graves, Aggie stumbles upon the unsolved murder of a young woman--the details of which match Mumsie's case. As Aggie exhumes the past's secrets, she uncovers a crime that some will go to any length to keep quiet--even if it means silencing Aggie. In 1946, Imogene Flannigan works in a local factory and has eyes on owning her own beauty salon. But coming home to discover her younger sister's body in the attic changes everything. Unfamiliar with the newly burgeoning world of criminal forensics and not particularly welcomed as a woman, Imogene is nonetheless determined to stay involved. As her sister's case grows cold, Imogene vows to find justice . . . even if it costs her everything."--